Support methodology to the informational and conceptual design of small recreational powerboats (Human Factors in Design, 2024)
This article proposes a methodology for the design of motor recreational boats which are a crucial part of the Brazilian nautical industry. Despite the high demand for these boats, design methodologies for small leisure vessels are not well explored in the literature, leading to not mapped aspects as design information treatment, requirements engineering, and trade-off conflicts. The proposed methodology aims to systematize the obtaining of design specifications, generation and evaluation of solution concepts, employing de- sign support tools. The methodology was evaluated by applying it on a small recreational motorboat, and the results were positively evaluated by nautical industry and academic specialists, leading to acceptation of the methodology and some suggestions for improvement.
Keywords: product development; small boat design methodology; motor boat design; information design; conceptual design